The Role of Bloodletting and Cupping in Severe Acute Urticaria and Angioedema as Skin Emergencies in Persian Medicine - Maryam Taghavi Shirazi; Hoorieh Mohammadi Kenari; Fatemeh Eghbalian (Korean Pharmacopuncture Institute, 2022)
Objectives: Some dermatological diseases can be life-threatening. Urticaria and angioedema are common reasons for patients to seek treatment at an emergency department. Severe, generalized urticaria and angioedema can endanger patients' lives by involving the airways and causing anaphylactic shock. The humor-based Persian Medicine (PM) concepts of Shara andMaShara, referring to two kinds of skin lesions, have similarities to urticaria and angioedema, respectively. This article aims to provide scientific evidence regarding the application of PM as an early intervention strategy in the emergency management of urticaria and angioedema. Methods: This was a narrative review of PM studies identified by searching medical databases using search terms related to these diseases, as well as risk-associated keywords such as "fatal", "death", "life-threatening", "emergency", "cupping", and "bloodletting". Data were then compared, interpreted, and analyzed. Results: PM scholars consider the human body as a unified whole and believe in an inner power (Nature) which stems from the body. When the presence of excessive hot substances cause an imbalance of bodily humors, Nature directs their heated vapors sharply toward the skin, thus causing Shara andMaShara. If there is a high risk of inflammation spreading to vital organs under severe conditions, urgent manual interventions are crucial. Conclusion: In serious conditions of urticaria and angioedema, Fasd or bloodletting and Hijama can be effective in speeding up the control of lesions and reducing morbidity and mortality. Consequently, the development of integrated Persian and conventional medicines may provide new therapeutic pathways for skin emergencies.